Effect of type and concentration of solvent on chemical properties of saffron edible extract. Issue 1 (2014) - Ali Mohamadi Sani; Sharare Mohseni
<x xml:space="preserve"> Abstract </x> Purpose – The purpose of this study was to find a suitable solvent to produce saffron edible extract with improved chemical properties. Design/methodology/approach – Dried and pulverized stigmas of Crocus sativus L. (10 g) was extracted with 300 ml of solvents including distillated water (DW), ethanol/DW, methanol/DW, propylene glycol/DW, heptan/DW and hexan/DW, for three days at 25°C and then centrifuged at 3, 000 rpm. Then, the extracts were evaporated using rotary evaporator at 40°C. The fiber and solvent‐free extracts were then analyzed by UV spectrophotometer to detect saffron quality parameters including crocin, picrocrocin and safranal. Findings – Distilled water/ethanol mixture as the extraction solvent caused larger amounts of the plant constituents to diffuse out to the extract compared to other treatments and also control. Polar solvents including distilled water, ethanol and propylene glycol (except methanol) were more effective in extracting crocin, picrocrocin and safranal than non‐polar solvents. Originality/value – No research had been done on production of saffron edible extract using the solvent studied in this survey. The novelty of this research is high and the results can be used industrially. <ack> <x xml:space="preserve"> Acknowledgements </x> The authors are thankful to Islamic Azad University, Quchan Branch for financial support of this research. </ack>